2019
DOI: 10.3347/kjp.2019.57.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Four Year Surveillance of the Vector Hard Ticks for SFTS, Ganghwa-do, Republic of Korea

Abstract: The seasonal abundance of hard ticks that transmit severe fever with thrombocytopenia syndrome virus was monitored with a collection trap method every April to November during 2015-2018 and with a flagging method every July and August during 2015-2018 in Ganghwa-do (island) of Incheon Metropolitan City, Republic of Korea. This monitoring was performed in a copse, a short grass field, coniferous forest and broad-leaved forest. A total of 17,457 ticks (8,277 larvae, 4,137 nymphs, 3,389 females, and 1,654 males) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
4
19
1
Order By: Relevance
“…Previous studies have shown that the number of SFTS patients infected by the environment were more than those who were infected by ticks [ 19 , 30 33 ]. But most studies only use the density of ticks in the environment and the antibody of SFTSV in ticks to evaluate the hazardous situation of the environment [ 22 , 48 50 ], so they did not consider the environment as one of the transmission route. As we all know, several factors such as the number of ticks, the dominant phase of ticks, outdoor activities and the change of weather can affect the occurrence of SFTS [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the number of SFTS patients infected by the environment were more than those who were infected by ticks [ 19 , 30 33 ]. But most studies only use the density of ticks in the environment and the antibody of SFTSV in ticks to evaluate the hazardous situation of the environment [ 22 , 48 50 ], so they did not consider the environment as one of the transmission route. As we all know, several factors such as the number of ticks, the dominant phase of ticks, outdoor activities and the change of weather can affect the occurrence of SFTS [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches suggested that ticks are the main host of SFTS and play a key role in its transmission. Haemaphysalis longicornis , Ixodes nipponensis , Rhipicephalus microplus and Dermacentor sinicus , amongst others, are the susceptible ticks identified, but Haemaphysalis longicornis is the dominant species [ 1 , 19 22 ]. While SFTS cases occurred from March to November, the disease period peaked in August and September.…”
Section: Introductionmentioning
confidence: 99%
“…nipponensis , which is associated with both grass/herbaceous vegetation and forested habitats, was also less prevalent [ 22 ]. As dogs are more likely to enter grass/herbaceous vegetation than forests, they are exposed to H. longicornis ticks more frequently in the ROK [ 22 , 23 , 24 ]. However, a previous study reported that only I. nipponensis ticks were collected from dogs in the Gyeongsangbuk province [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the number of SFTS patients infected by the environment were more than those who were infected by ticks [17,31,32,33,34]. But most studies only use the density of ticks in the environment and the anti-body of SFTSV in ticks to evaluate the hazardous situation of environment [46,47,48,49], so they do not consider the environment as one of the transmission routes. As we all know, several factors such as the number of ticks, the dominant phase of ticks, outdoor activities and the change of weather can affect the occurrence of SFTS [50].…”
Section: The Effect Of Cutting Different Transmission Routesmentioning
confidence: 99%